1995
DOI: 10.1074/jbc.270.32.18975
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Magnesium-binding Domain of the High-affinity ATP-binding Site of the Bacillus subtilis and Escherichia coli SecA Protein

Abstract: The homodimeric SecA protein is the peripheral subunit of the translocase, and couples the hydrolysis of ATP to the translocation of precursor proteins across the bacterial cytoplasmic membrane. The high affinity ATP binding activity of SecA resides in the amino-terminal domain of SecA. This domain contains a tandem repeat of the "so-called" Walker B-motif, hXhhD (Walker, J.E., Saraste, M., Runswick, M.J., and Gay, N.J. (1982) EMBO J. 1, 945-951), that in combination with motif A is responsible for the Mg(2+)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…Binding of Mg 2烯 and Mn 2烯 Metal Ions to the HCV NS5B Protein-The binding of metal ions to free enzymes has been shown to result in a significant decrease in emission fluorescence intensities (31)(32)(33). We observed that the binding of both Mg 2烯 and Mn 2烯 ions to the NS5B protein resulted in a modification of the intensity of the intrinsic fluorescence of this protein.…”
Section: Fig 2 Titration Of Ns5b With Mgmentioning
confidence: 82%
“…Binding of Mg 2烯 and Mn 2烯 Metal Ions to the HCV NS5B Protein-The binding of metal ions to free enzymes has been shown to result in a significant decrease in emission fluorescence intensities (31)(32)(33). We observed that the binding of both Mg 2烯 and Mn 2烯 ions to the NS5B protein resulted in a modification of the intensity of the intrinsic fluorescence of this protein.…”
Section: Fig 2 Titration Of Ns5b With Mgmentioning
confidence: 82%
“…Specifically, the broadening of resonances arising from both mobile segments upon addition of Mn 2烯 indicates that both mobile regions 1 and 2 are close to the Mg 2烯 -binding site, which is proposed to involve residues Asp 209 and Asp 217 (35). The proximity of mobile region 1 to these residues is not surprising, given the observed direct interactions between these segments in the structure (21), but these data provide the first direct evidence that the extreme C-terminal region of SecA (unresolvable in the crystal structure) approaches closely to the interface between NBF-I and -II.…”
Section: Locations Of Assigned Arginines Indicated By Open Circles)mentioning
confidence: 99%
“…The specific activity of these mutant proteins was less than onetenth that of the wild-type protein. DnaA A184V, DnaA46, and DnaA5 required longer incubation periods for expression of replication activity; the time lag for DNA replication reaction for these mutant DnaA proteins has been reported (16,17,27). In the case of DnaA K178I and DnaA D235N, the time course of DNA replication is approximately linear, as is the case for the wild-type protein (Fig.…”
Section: Table Imentioning
confidence: 76%